Optimisation of second stage dilute acid hydrolysis of oil palm fronds into glucose - Nekoui, Soheil (2014)
In this study, the potential of OPF as a lignocellulosic feedstock to produce fermentable sugars using two-stage dilute-acid hydrolysis was assessed. The proximate analysis revealed that OPF fibre was composed of 32.93% cellulose,29.91% hemicellulose and 19.53% lignin. This study focused on the hydrolysis of cellulose fraction of OPF into glucose in the second-stage of two-stage dilute acid hydrolysis. The second stage reactions were carried out above 150 °C. Four parameters that affect the yield of glucose, namely acid concentration, reaction temperature, reaction time and liquid to solid ratio were investigated. The batch reactions were carried out under different operating conditions as proposed by the experimental design generated by the Response Surface Methodology (RSM). The RSM was used to determine the optimum point for the second stage dilute acid hydrolysis process. In the first stage of dilute acid hydrolysis 4.33 g/L (33% yields) glucose was recovered. From the second stage hydrolysis, at optimum condition of 150 °C temperature, 6 % sulphuric acid concentration, 62 min of reaction time and a liquid/solid ratio of 28:1, the glucose yield was 4.48 g/L (34%). The amount of generated inhibitor (HMF and furfural) was 0.22 g/l. The total glucose yield from both stages of the two-stage hydrolysis process under optimum conditions was 67%. The kinetics study on the formation of glucose from dilute acid hydrolysis of OPF revealed that the reaction was a first order irreversible reaction. Based on the values of rate constants, it was found that the rate of formation of glucose (k1) was more dominant than the rate of degradation (k2). The activation energy values at the optimum acid concentration of 6% were 85.733 kJ/mol for glucose formation and 123.238 kJ/mol for glucose degradation. The n value for glucose formation at 150 °C was 0.647 while for glucose degradation was at 0.487. The findings of this study suggest that the glucose yield can be increased while the inhibitor formation can be decreased by increase in acid concentration and decrease in reaction temperature.